О. П. Реєнт. Українська революція і робітництво - Курило, В. М.; Лисенко, О. Є. (Український історичний журнал, 2025)
О. П. Реєнт. Українська революція і робітництво. К.: Поліграфкнига, 1996. — 265 с.